Infektionen - Lorenz, Hanns-Martin; Kneitz, Christian (Zeitschrift für Rheumatologie, 2019)
The individual risk assessment concerning infections in patients with rheumatic diseases is based on the detailed personalized documentation of relevant risk factors, such as the underlying disease itself, the intensity of immunosuppressive therapy and the severity of any comorbidities. From the perspective of infectiology, the history of repeated and severe infections as well as previous illnesses, such as (latent) tuberculosis and chronic hepatitis B or C need to be considered. In some instances prophylactic antibiotic therapy might be required, which should otherwise be avoided in order to prevent selection of resistant pathogens. Furthermore, vaccinations are particularly suitable to specifically minimize the risk for frequent infectious diseases.
Gesehen am 28.01.2020